The Effects of Thinking Empowerment by Questioning in Biology Learning on Problem-Solving Ability - Sudianto Sudianto; Nining Purwati; Ali Harris (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
The low level of problem-solving ability requires innovation in learning to overcome it. One of them is through the implementation of the Thinking Empowerment by Questioning learning strategy. This study aims to examine the impact of Thinking Empowerment through Questioning techniques on biology learners' capacity for problem-solving—this type of quasi-experimental research with a quantitative approach and design pretest-posttest experimental control group design. The research was conducted at SMAN 1 Bayan, North Lombok Regency. The population used was all grade X with 288 students. Samples were taken by cluster random sampling technique, with class XA as the experimental class, and class XC as the control class.  The instrument used is an essay-shaped test on environmental change material totalling 10 questions. Data analysis technique using Analysis of Covariance test with the help of SPSS 26 software. The result of the Analysis of Covariance shows a significance value of 0.000 <0.05. This means the Thinking Empowerment by Questioning strategy has a significant effect on problem-solving ability in biology learning on environmental change material at SMAN 1 Bayan. The significant result can be a reference for teachers to improve problem-solving ability through the application of the TEQ strategy